Association between cannabis use with urological cancers: A population‐based cohort study and a mendelian randomization study in the UK biobank. (17th August 2022) - Huang, Jingyi; Huang, Da; Ruan, Xiaohao; Huang, Jinlun; Xu, Danfeng; Heavey, Susan; Olivier, Jonathan; Na, Rong
Abstract: Background: Legislation of cannabis use has been approved in many European and North American countries. Its impact on urological cancers is unclear. This study was conducted to explore the association between cannabis use and the risk of urological cancers. Methods: We identified 151, 945 individuals with information on cannabis use in the UK Biobank from 2006 to 2010. Crude and age‐standardized incidence ratios of different urological cancers were evaluated in the entire cohort and subgroups. Cox regression was performed for survival analysis. Results: Previous use of cannabis was a significant protective factor for renal cell carcinoma (HR = 0.61, 95%CI:0.40–0.93, p  = 0.021) and prostate cancer (HR = 0.82, 95%CI:0.73–0.93, p  = 0.002) in multivariable analysis. The association between previous cannabis use and both renal cell carcinoma and bladder cancer was only observed in females (HRRCC  = 0.42, 95%CI:0.19–0.94, p  = 0.034; HRBCa  = 0.43, 95%CI:0.21–0.86, p  = 0.018) but not in men. There was no significant association between cannabis use and testicular cancer incidence. Mendelian randomization demonstrated a potential causal effect of cannabis use on a lower incidence of renal cell carcinoma. Conclusions: Previous use of cannabis was associated with a lower risk of bladder cancer, renal cell carcinoma, and prostate cancer. The inverse association between cannabis and both renal cell carcinoma and bladder cancer was only found in females but not in males. Abstract : Previous cannabis use had a inverse association with BCa, RCC and PCa. For BCa and RCC, the effect of cannabis use was significant in females but not in males.